The Influence of Spousal Support on Anxiety Among Women in the Third Trimester of Pregnancy at the Momalia Community Health Center - Vira Cikita Landa; Tut Rayani Aksohini Wijayanti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Anxiety during the third trimester of pregnancy is a prevalent perinatal mental health issue that can adversely affect maternal well-being and preparedness for labor. Psychosocial factors, particularly partner support, are recognized as important in alleviating anxiety; however, empirical evidence at the primary healthcare level in Indonesia is still limited. This study aimed to analyze the relationship between partner support and anxiety levels among third-trimester pregnant women receiving care at the Momalia Community Health Centre. A quantitative analytical approach with a cross-sectional design was employed. The study involved 60 third-trimester pregnant women selected through total sampling. Partner support was assessed using a structured social support questionnaire, while maternal anxiety was measured using a standardized, valid, and reliable instrument. Data analysis included descriptive and inferential statistics, with the relationship between variables tested using the Chi-square test at a significance level of 0.05. The results revealed a statistically significant association between partner support and maternal anxiety (p < 0.05). Women who reported higher levels of partner support tended to experience lower anxiety, whereas those with inadequate support showed higher levels of moderate to severe anxiety. In conclusion, partner support serves as a protective factor against anxiety during late pregnancy. Integrating husbands’ involvement into antenatal care programs is essential to enhance maternal mental health outcomes.